Oficina de produção de instrumentos musicais: um estudo de caso na concepção Deweyana da experiência - Santos, Manoel Tadeu Alves dos (2019)
This study aimed to identify and evaluate possibilities of contributing to the teaching and learning process, from a proper environment for a reconciliation of theorical and pratical, interdisciplinary and transdisciplinary activities. Therefore, in order to facilitate the monitoring and observation of the actions undertaken by the participants, we implemented an augmented product to the development of such activities: the “Musical Instrument Production Workshop” (OPIM), which is the object of the research; having as target audience the students and graduates of the technical courses in electrotechnics and mechanics of the Instituto Federal do Espírito Santo, campus São Mateus. Based on the qualitative research, the methodology adopted prioritized the use of Unsystematic Participant Observation, as Case Study. With the purpose of providing students with an opportunity for active, autonomous and democratic participation and immersion in activities, the conduction of this research was based on the Dewey’s Theory of Educative Experience. The production of data was done through several means namely: logbooks (individual and collective), audio visual records, semi-structured questionnaire and, mainly, observation and follow-up of the researcher. It is noteworthy that, in order to provide greater fluency of interaction and collaboration between students and, in order to favor the exercise of educational autonomy and democracy, We opted for the minimal intervention of the researcher in the creative process of the ‘workshoppers’. Therefore, based on the perspectives of the Dewey’s Pedagogy of Projects, the analysis and results showed that the opportunity to reconcile prior knowledge with the technical contents acquired (or in acquisition) provided students with new possibilities for meaning in learning and (re)construction of knowledge. Since for most ‘workshoppers’, similar activities – that is, “learning by doing” through experience – can contribute positively to the processes of knowledge acquisition, meaning and retention. But even if some students may not feel able to exercise their autonomy and freedom of action in the learning process itself, the careful and more individualized monitoring of the teacher may gradually serve as a as triggering elements of their “educative interest”. Considering, therefore, the persistent tendency of technical and vocational education to preserve certain dualities and rigidity in its teaching plans, it was concluded that the proposal under analysis can contribute, even if minimally, as an integrative didactic alternative, capable of reconciling the methods current didactics.